Are primary care nurses trained to detect gender-based violence? - Diana de la Fuente Aparicio; Ana Belén Salamanca Castro; Sara Sánchez Castro (Fundación para el Desarrollo de la Enfermería, 2005)
Domestic violence is one of the main causes of death and traumatisms, and has become an important public health problem. In the last years, both the number of casualties and formal complaints due to gender-based violence have increased. This problem can be prevented and nurses play an essential role in its diagnosis and prevention due to the close relationship between them and the patients suffering this type of problem.Objective: To explore whether primary care nurses are able to detect gender-based violence.Methodology: In order to explore the professionals' approach, a qualitative approach based on focus group interviews was designed. The participants' characteristics were recorded using a specific questionnaire. Results: Domestic violence can be detected in patients who establish a close relationship with Primary Care nurses. In order to get people suffering gender-based violence talk about their problem, a close relationship is mandatory.Discussion: Starting a new life far from the aggressor cannot be defined as the only success criteria for nurses attending people who suffer gender-based violence. Leaving or not the aggressor must be decided only by the victims.